2012
DOI: 10.4161/derm.20332
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of vitamin D supplementation in adults with cystic fibrosis pulmonary exacerbation

Abstract: Background: Vitamin D insufficiency is common in cystic fibrosis (CF) and vitamin D repletion may have an important role in improving clinical outcomes in CF. This randomized, placebo-controlled, pilot study examined the feasibility and impact of a single, large dose of cholecalciferol on vitamin D status and clinical outcomes in subjects with CF. Methods: Thirty adults with were randomized in a double-blinded, pilot study to receive 250,000 IU cholecalciferol or placebo within 48 h of hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 35 publications
5
58
1
2
Order By: Relevance
“…In infants, it has been shown that low vitamin D in cord blood samples at birth is associated with higher incidence of respiratory syncytial virus (6), and infants readmitted to the neonatal intensive care unit with acute lower respiratory tract infection had lower vitamin D levels than age-matched control subjects (7). In adults with CF, those who received a high dose of cholecalciferol (250,000 IU) once at the time of admission for a pulmonary exacerbation had significantly fewer hospitalizations for pulmonary exacerbations over the next 6 months compared with those receiving placebo (36). Combined, these studies suggest that vitamin D may prevent viral infection and possibly work as an adjunct treatment to antibiotics to decrease the severity of an exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…In infants, it has been shown that low vitamin D in cord blood samples at birth is associated with higher incidence of respiratory syncytial virus (6), and infants readmitted to the neonatal intensive care unit with acute lower respiratory tract infection had lower vitamin D levels than age-matched control subjects (7). In adults with CF, those who received a high dose of cholecalciferol (250,000 IU) once at the time of admission for a pulmonary exacerbation had significantly fewer hospitalizations for pulmonary exacerbations over the next 6 months compared with those receiving placebo (36). Combined, these studies suggest that vitamin D may prevent viral infection and possibly work as an adjunct treatment to antibiotics to decrease the severity of an exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPs contain vitamin D-responsive elements (VDRE) in their gene promoter, whereby vitamin D is directly inducing LL-37 and β-defensin gene expressions [34]. Furthermore, a positive correlation between serum vitamin D levels and lung function [41] in CF patients as well as improved clinical outcomes in CF patients with pulmonary exacerbation have been demonstrated [42].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for extra-skeletal functions of vitamin D in CF is accumulating. For example, vitamin D is likely to improve respiratory function through its role in antimicrobial peptide and cytokine production and its association with muscle strength [40,41,43,44]. It is also associated with CFRD through potential involvement in islet function regulation, insulin production and secretion, and insulin sensitivity [42,46].…”
Section: Fat-soluble Vitaminsmentioning
confidence: 97%
“…PTH, concurrent with serum calcium, phosphorus and 1,25(OH) 2 D itself, tightly regulates serum 1,25(OH) 2 D levels. Absorption and metabolism of vitamin D seem to vary according to supplement formulation as well [44,46,48,52,53]. Animal-derived cholecalciferol (vitamin D 3 ) [53] appears to outperform plant-derived ergocalciferol (vitamin D 2 ) [48,52,54] at much lower dosages in normalising serum 25(OH)D levels in adults with CF.…”
Section: Fat-soluble Vitaminsmentioning
confidence: 97%